Bacterial Isolates and Their Antibiotics Susceptibility Pattern Among Patients Admitted With Chronic Lower Limb Ulcers at Kilimanjaro Christian Medical Centre Northern Zone Referral Hospital, Tanzania. (December 2021) - Hape, Wilson Marco; Magambo, Mujuni Josephat; Ngocho, James Samwel; Mosha, Victor; Msuya, Sia E.; Leyaro, Beatrice John
Objective . To identify the bacterial isolates and their antibiotics susceptibility pattern among patients with lower limb ulcers admitted at a tertiary hospital in northern Tanzania. Methodology. A cross-sectional study was conducted between April and July 2018 at the Kilimanjaro Christian Medical Centre. Questionnaire was used to obtain the demographics and clinical information of participants. Wound samples were collected and culture method used to identify the bacteria and their susceptibility patterns. Results. Out of 65 participants, 55 (84.6%) had positive aerobic bacterial growth. Twelve (18 %) participants had more than one bacterium. Fifty-nine (88.1%) were gram-negative bacteria. Proteus vulgaris (13, 19.9%), Pseudomonas spp (10, 14.8%), and Staphylococcus aureus (8, 11.7%) were the common isolates. Out of 59 gram-negative bacterial, 47 (78%) were sensitive to amikacin. Staph were sensitive to oxacillin (75%; n = 8) and vancomycin (50%; n = 8). Gram-negative were common isolates and were resistant to amoxicillin/clavulanic acid but sensitive to amikacin. Conclusion . The observed resistance to antibiotics calls for continuous monitoring of the resistance pattern to guide the empirical management of patients with leg ulcer.